2020
DOI: 10.3389/fendo.2020.00369
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Role of Osteocalcin in Human Arterial Smooth Muscle Cell Calcification

Abstract: Osteocalcin (OCN) is a bone-derived protein that is detected within human calcified vascular tissue. Calcification is particularly prevalent in chronic kidney disease (CKD) patients but the role of OCN in calcification, whether active or passive, has not been elucidated. Part 1: The relationship between OCN, CKD and vascular calcification was assessed in CKD patients (n = 28) and age-matched controls (n = 19). Part 2: in vitro, we analyzed whether addition of uncarboxylated osteocalcin (ucOCN) influenced the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In total, eighteen studies were performed investigating an association between osteocalcin and arterial calcification ( Barbarash et al, 2016 ; Golovkin et al, 2016 ; Liu et al, 2019 ; Pirro et al, 2013 ; Torii et al, 2016 ; Awan et al, 2010 ; Bernandes et al, 2019 ; Kim et al, 2012 ; Watson et al, 1997 ; Salari et al, 2017 ; Wilund et al, 2008 ; Miyabara et al, 2011 ; Zwakenberg et al, 2020 ; Choi et al, 2015 ; Kim et al, 2016 ; Millar et al, 2020 ; Cahalane et al, 2021 ; Zhelyazkova-Savova et al, 2021 ). Two studies reported a positive association ( Liu et al, 2019 ; Salari et al, 2017 ), five a negative association ( Golovkin et al, 2016 ; Awan et al, 2010 ; Kim et al, 2012 ; Wilund et al, 2008 ; Cahalane et al, 2021 ) and eleven no association ( Barbarash et al, 2016 ; Pirro et al, 2013 ; Torii et al, 2016 ; Bernandes et al, 2019 ; Watson et al, 1997 ; Miyabara et al, 2011 ; Zwakenberg et al, 2020 ; Choi et al, 2015 ; Kim et al, 2016 ; Millar et al, 2020 ; Zhelyazkova-Savova et al, 2021 ). One longitudinal study reported higher osteocalcin in people with a calcified coronary or carotid plaque after five years of follow-up in 1571 participants, ≥60 years of age, without plaque at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…In total, eighteen studies were performed investigating an association between osteocalcin and arterial calcification ( Barbarash et al, 2016 ; Golovkin et al, 2016 ; Liu et al, 2019 ; Pirro et al, 2013 ; Torii et al, 2016 ; Awan et al, 2010 ; Bernandes et al, 2019 ; Kim et al, 2012 ; Watson et al, 1997 ; Salari et al, 2017 ; Wilund et al, 2008 ; Miyabara et al, 2011 ; Zwakenberg et al, 2020 ; Choi et al, 2015 ; Kim et al, 2016 ; Millar et al, 2020 ; Cahalane et al, 2021 ; Zhelyazkova-Savova et al, 2021 ). Two studies reported a positive association ( Liu et al, 2019 ; Salari et al, 2017 ), five a negative association ( Golovkin et al, 2016 ; Awan et al, 2010 ; Kim et al, 2012 ; Wilund et al, 2008 ; Cahalane et al, 2021 ) and eleven no association ( Barbarash et al, 2016 ; Pirro et al, 2013 ; Torii et al, 2016 ; Bernandes et al, 2019 ; Watson et al, 1997 ; Miyabara et al, 2011 ; Zwakenberg et al, 2020 ; Choi et al, 2015 ; Kim et al, 2016 ; Millar et al, 2020 ; Zhelyazkova-Savova et al, 2021 ). One longitudinal study reported higher osteocalcin in people with a calcified coronary or carotid plaque after five years of follow-up in 1571 participants, ≥60 years of age, without plaque at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…International literature data about the effects of osteocalcin on vascular calcification and stabilization/destabilization of atherosclerotic plaques are contradictory. For instance, the results of Millar et al imply that osteocalcin is not a mediator of vascular calcification [ 17 ]. Rashdan et al showed the colocalization of osteocalcin with the calcification of smooth muscle cells in calcified plaques and pointed out the crucial role of osteocalcin in arterial calcification [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies have reported the association of OC with the later stages of atherosclerotic plaque development, calcification and CVD events, often with conflicting findings [ 14 , [17] , [18] , [19] ]. However, given the importance of blood vessel dysfunction in the development of atherosclerosis, an increasing number of studies have begun to investigate the association of OC with endothelial and smooth muscle cell function ( Table 1 ) [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. These studies will be discussed at length below.…”
Section: The Association Between Oc and Blood Vessel Function In Humamentioning
confidence: 99%
“…In contrast, higher tOC was associated with higher PWV in men and women with end-stage renal disease on peritoneal dialysis [ 27 ]. Whereas, in both men and women with stage 3 and 4 chronic kidney disease (CKD), no association was reported between tOC and PWV [ 20 ]. Several studies have also examined the association of tOC with endothelial function ( Table 1 ).…”
Section: The Association Between Oc and Blood Vessel Function In Humamentioning
confidence: 99%